Further investigations into alloy induced acidic fluxing - Potter, Andrew; Sumner, Joy; Simms, Nigel J. (Taylor & Francis, 2023)
Gas turbine materials often feature precipitates containing refractory metals to enhance their mechanical strength. This can make them susceptible to alloy-induced acidic fluxing whereby refractory elements increase the acidity of salt deposits. It is not clear to what degree degradation around alloy precipitates is caused by alloy-induced hot corrosion mechanisms, or the inability to develop a protective scale where precipitates are located. The effect of alloy-induced hot corrosion was isolated from the disruption of the protective-scale formation by adding particles of molybdenum to the 80/20 (Na/K)2SO4 deposit for a ‘deposit re-coat’ style hot corrosion test. The resulting morphologies were compared to samples exposed without the addition of molybdenum. Morphology changes were investigated using scanning electron microscopy with energy-dispersive X-ray mapping. Results show a mix of sulphidation and pitting. The effects of molybdenum additions appear more severe for MarM 509 compared to PWA 1483.
Keywords: Type II hot corrosion; superalloys; alloy-induced acidic fluxing; mixed mode hot corrosion